IDEALITA DAN REALITA DALAM DUNIA PENERJEMAHAN - Abdul Malik (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
The question whether communicating message can be done correctly in a translation process is a problematic issue. The process of translating is not only doing the conversion of text from one language to another, but also communicating the message, which is culturally bounded. Translators always risk inappropriate spill-over of source-language idioms and forms into the target-language translation. On the other hand, spill-overs have imported useful source language calques and loanwords that have enriched the target languages. Indeed, translators have helped substantially to shape the languages into which they have translated.